Penerapan Pembelajaran Diferensiasi Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas XII SMA Xaverius 1 Jambi Tahun Pelajaran 2023/2024 (Implementasi Kurikulum Merdeka - Agun Sutrianto; Rayandra Asyhar (Departement of Mathematics Education, 2023)
This research aims to improve students' mathematics learning outcomes using a differentiated learning approach in the twelfth grade at SMA Xaverius 1 Jambi. This study employs a Classroom Action Research design, with the research subjects being the twelfth-grade class XII-5 Phase F. The research is conducted in two cycles. Data for the research results are obtained from mathematics learning outcome tests for students and observations of student attitudes during the learning activities using observation sheets and documentation. Data analysis techniques involve both qualitative and quantitative analyses. The research results indicate an improvement in the mathematics learning outcomes of twelfth-grade students in SMA Xaverius 1 Jambi. The percentage improvement in student learning outcomes exceeds the Minimum Mastery Criteria (KKTP) for each cycle. In cycle I, the percentage of students above the KKTP is 72.22%, and in cycle II, it increases to 86.11%. The conclusion drawn from this research is that the implementation of differentiated learning can enhance students' mathematics learning outcomes.